Dolutegravir plus rilpivirine: benefits beyond viral suppression - Jesús Troya, MD, PhD; Carlos Dueñas, MD; Idoia Irazola, MD; Ignacio de los Santos, MD, PhD; Sara de la Fuente, MD, PhD; Desiré Gil, MD, PhD; Cristina Hernández, MD; María José Galindo, MD, PhD; Julia Gómez, MD; Elisabeth Delgado, MD; Estela Moreno-García, MD; Guillermo Posada, MD, PhD; et al. (Medicine, 2022)
Abstract. Switching dual therapy with dolutegravir (DTG) plus rilpivirine (RPV) was assessed in the SWORD-1 and SWORD-2 studies. Real-life data regarding the immunological impact of this approach on CD4+ and CD8+ T lymphocyte counts and the CD4/CD8 ratio are scarce. We evaluated this strategy on the basis of clinical practice data. A multicentric retrospective cohort study. Treatment-experienced virologically suppressed HIV-1-infected patients who were switched to DTG plus RPV were included. Using different models for paired data, we evaluated the efficacy and immune status in terms of CD4+ and CD8+ T-cell counts and CD4/CD8 ratio at 24 and 48 weeks of treatment. The study population comprised of 524 patients from 34 centers in Spain. Men accounted for 76.9% of patients, with a median age of 53 years. Patients receiving DTG plus RPV reached weeks 24 and 48 in 99.4% and 83.8% of cases, respectively, with only three (0.57%) virological failures. We found a significant decrease in CD8+ T-cell count (log OR –40) at week 24 and an increase in CD4+ T-cell count at week 48 (log OR +22.8). In acquired immunodeficiency syndrome-diagnosed patients, we found a significant increase in the CD4+ T-cell count at week 48 (log OR = 41.7, P = .0038), but no significant changes in the CD8+ T-cell count (log OR = –23.4, P = .54). No differences were found in the CD4/CD8 ratio between the acquired immunodeficiency syndrome subgroup and sex or age. In patients with controlled treatment, dual therapy with DTG plus RPV slightly improved the immune status during the first 48 weeks after switching, not only in terms of CD4+ T-cell count but also in terms of CD8+ T-cell count, with persistently high rates of viral control.